Synthesis, Antioxidant and In-Silico Studies of Potent Urease Inhibitors: N-(4-{[(4-Methoxyphenethyl)-(substituted)amino]sulfonyl}phenyl)acetamides - Abbasi, Muhammad Athar; Raza, Hussain; Rehman, Aziz ur; Siddiqui, Sahahat Zahra; Nazir, Majid; Mumtaz, Ayesha; Shah, Syed Adnan Ali; Seo, Sung-Yum; Hassan, Mubashir (Drug Research, 2019)
In this study, a new series of sulfonamides derivatives was synthesized and their inhibitory effects on DPPH and jack bean urease were evaluated. The in silico studies were also applied to ascertain the interactions of these molecules with active site of the enzyme. Synthesis was initiated by the nucleophilic substitution reaction of 2-(4-methoxyphenyl)-1-ethanamine (1) with 4-(acetylamino)benzenesulfonyl chloride (2) in aqueous sodium carbonate at pH 9. Precipitates collected were washed and dried to obtain the parent molecule, N-(4-{[(4-methoxyphenethyl)amino]sulfonyl}phenyl)acetamide (3). Then, this parent was reacted with different alkyl/aralkyl halides, (4a-m), using dimethylformamide (DMF) as solvent and LiH as an activator to produce a series of new N-(4-{[(4-methoxyphenethyl)-(substituted)amino]sulfonyl}phenyl)acetamides (5a-m). All the synthesized compounds were characterized by IR, EI-MS, 1H-NMR, 13C-NMR and CHN analysis data. All of the synthesized compounds showed higher urease inhibitory activity than the standard thiourea. The compound 5 f exhibited very excellent enzyme inhibitory activity with IC50 value of 0.0171±0.0070 µM relative to standard thiourea having IC50 value of 4.7455±0.0546 µM. Molecular docking studies suggested that ligands have good binding energy values and bind within the active region of taget protein. Chemo-informatics properties were evaluated by computational approaches and it was found that synthesized compounds mostly obeyed the Lipinski’ rule.
Keywords: Sulfonamides; acetamides; alkyl/aralkyl halides; spectral analysis; antioxidant; Urease inhibition; Molecular docking